First record of Leucania herrichii Herrich-Schäffer from Iran with new distribution data of Leucaniini (Lep., Noctuidae) - Behnaz Ravan; Mehdi Esfandiari; Mohammad Saeed Mossadegh (Journal of Insect Biodiversity and Systematics, 2024)
The larvae of certain species in the Noctuidae family cause significant economic damage annually. Due to the importance of this group, specimens of the subfamily Noctuinae, specifically from the tribe Leucaniini, collected from the Fars, Ilam, Kerman and Khuzestan provinces were studied. As a result, among the nine identified and studied species from the genera Mythimna and Leucania, four species from Khuzestan province, three species from Ilam province and one species from Fars province were registered as new provincial records. Additionally, the distribution of Leucania (Leucania) herrichii Herrich-Schäffer, 1849 was confirmed for the first time in Iran. Further studies on this tribe in different parts of Iran are recommended.